A SOCIAL STRATEGY OF UNIVERSITY LEARNERS OF LOW-LEVEL SPEAKING PROFICIENCY - Restu Mufanti (Universitas Muhammadiyah Ponorogo, 2014)
This study is to investigate the learning strategies applied by low-level leaners (LLLs), the results of which can be used as the basis for placing them in an English language speaking class. Specifically this study is to find an answer To what extent do low-level leaners use social strategies in learning to speak English?? Observation and an in-depth interview wereused to collect the data which were in the form of the subjects? spoken utterances (verbal behavior) and their accompanying actions (non-verbal behavior). The data were analyzed using the social language learning strategies (SLLS) proposed by Rebecca Oxford. Three universityleaners from the third semester who are of the same level of proficiency were selected as the subjects of the study. Results of the data analysis show that the LLLs do not use all social strategies in speaking activities. Based on what has been shown by this study, it is suggestedthat supportive teacher behaviors, i.e., building leaners? confident, giving motivation during the teaching, listening attentively to students while speaking, giving hints and encouragement, being responsive to student questions, creating natural setting and showing students empathy need to be provided in speaking class activities to explore leaners social strategies.